Pengaruh Model Take and Give terhadap Hasil Belajar Siswa pada Subtema 1 Cara Tubuh Mengolah Udara Bersih di Kelas V SD Negeri 124385 Pematang Siantar tahun Ajaran 2022/2023 - Juni Agus Simaremare; Elsawita Ritonga; Partohap S.R Sihombing (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to determine the effect of using the Take and give learning model on learning outcomes in Subtheme 1 How the Body Processes Clean Air. This study uses a quantitative approach. to test the research instrument using Validity Test, Reliability, Difficulty level test, Distinguishing test. data collection with the observation stage, pre-test and administration and post-test. Data analysis techniques used the Mean, Variance, and Homogeneity test, as well as hypothesis testing with the t-test. The results showed: (1) The homogeneity test of the data with a significance value > 0.05 then it was said to be homogeneous if the sig-based mean value > 0.05. -the experimental class and the control post-test are the same or homogeneous. Based on these results can. (2) Output pair 2 obtained sig (2 tailed) value of 0.000, then 0.000 > 0.05. Based on these results, it can be concluded that H0 is rejected and Ha is accepted. Based on the research concluded: there is a positive and significant relationship the effect of the take and give model on student learning outcomes. These results are evidenced by the results of hypothesis testing with the t test formula, where t count obtained sig (2 tailed) value of 0.00 > 0.05 so that it can be concluded that Ho is rejected and Ha is accepted.